2020
DOI: 10.18844/cjes.v15i5.5167
|View full text |Cite
|
Sign up to set email alerts
|

Social health and environmental behavior of students in the digital age

Abstract: This paper describes the importance of theoretical understanding of modern social health, educational and environmental behavior of students in the digital age. The purpose of this research is to analyze the concepts and trends of social health and environmental behavior of students in the context of modern social digitalization process. The paper deals with the framework and methodology of modern social and philosophical theories devoted to the problems of digital society and digital technologies. The theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In articles on the problem of digital education in information and communication spheres, scientists concluded that the development of a creative personality in education is associated with the field of social health and the upbringing of students' ecological behavior, and the development of a digital society in education" [8].…”
Section: Methodsmentioning
confidence: 99%
“…In articles on the problem of digital education in information and communication spheres, scientists concluded that the development of a creative personality in education is associated with the field of social health and the upbringing of students' ecological behavior, and the development of a digital society in education" [8].…”
Section: Methodsmentioning
confidence: 99%
“…Information technology offers wide opportunities, including in education such as online education, access to educational e-resources, modern scientific publications, lectures by well-known scientists, etc. In this case, digital technologies play an important role in environmental education to shape students' environmental culture (Zakharova et al, 2020). The high school curriculum in Indonesia considers environmental education as a non-specific subject.…”
Section: Introductionmentioning
confidence: 99%
“…Whether higher or pre-higher, the school communities are great tools to actualise the biosphere stability for all generations continuously. Students, individuals, communities, government, Non-Governmental Organisations, and corporate organisations are the foremost advocates that can make this happen in this contemporary world [3]. It is vital to establish an effective and efficient waste control system to stabilise the environment for growth and advancement in various human endeavours [3].…”
Section: Introductionmentioning
confidence: 99%